2019
DOI: 10.3846/jbem.2019.11050
|View full text |Cite
|
Sign up to set email alerts
|

COOPERATIVE AND NON-COOPERATIVE R&D IN PRODUCT INNOVATION AND FIRM PERFORMANCE

Abstract: The aim of this article is to investigate the impacts of cooperative and non-cooperative R&D strategies on product innovation and firm performance. Based on the industrial economics literature and the optimisation model, R&D competition, R&D cartelisation, and full industry cartelisation strategies of firms operating on a market with differentiated goods and simultaneous price and quality competition are considered. It is showed that R&D cartelisation entails a loss of firm’s product innovation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 72 publications
(126 reference statements)
1
10
0
3
Order By: Relevance
“…globalization and innovation, so that companies should increase awareness of the value of knowledge about customers [45]. The study's findings by Bertrand and Mol [46] also support this research on antecedents and performance consequences on R&D. Karbowski [47], in his study, also explained that companies needed to maximize the advantages of competitive strategies in R&D. Innovation are also an important marketing strategy for companies to achieve excellence [48]. These studies also support the findings of testing the fourth hypothesis, showing that R&D had a significant positive effect on competitive position.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…globalization and innovation, so that companies should increase awareness of the value of knowledge about customers [45]. The study's findings by Bertrand and Mol [46] also support this research on antecedents and performance consequences on R&D. Karbowski [47], in his study, also explained that companies needed to maximize the advantages of competitive strategies in R&D. Innovation are also an important marketing strategy for companies to achieve excellence [48]. These studies also support the findings of testing the fourth hypothesis, showing that R&D had a significant positive effect on competitive position.…”
Section: Discussionsupporting
confidence: 60%
“…The study of Bertrand and Mol [46] analyzed differences in antecedents and performance reports on R&D. The results of the study found that the absorption capacity of R&D may lead to more positive innovation outcomes, particularly product innovation. Meanwhile, Karbowski [47] explained that the R&D process led to the emergence of product innovation compared to R&D competition. Companies that maximize profits from competitive strategies in R&D because companies prefer to pursue R&D cartelization or industrial cartelization strategies, depending on on-demand elasticity about the company's investment in R&D.…”
Section: The Effects Of Randd Resources On Innovation Orientation and Cmentioning
confidence: 99%
“…An important approach is that of innovation and new technological ventures. Karbowski (2019) suggests that a market with a high sensitivity to product quality improvements and a high competition will end up with the creation of a cartel. In addition, Monahan (2018) explores management alternatives with a behavioral economic lens and presents a new paradigm using Behavioral Sciences to account for the human factor.…”
Section: Overview Of Managerial Economicsmentioning
confidence: 99%
“…In this section, we consider the cooperation of firms in the R&D stage, but not on the final product market (the case of R&D cooperation, often called the R&D cartel, see, e.g., Kamien et al 1992;Kamien and Zang 2000;Karbowski 2019). The firms are assumed to behave non-cooperatively as Cournot players in the final product market.…”
Section: Randd Cooperationmentioning
confidence: 99%
“…The primary aim of this paper is to investigate the impact of patents and R&D cooperation on R&D investments made by firms. Since most of R&D investments refer to product markets with differentiated goods (Flath 2012;Rant and Černe 2017;Karbowski 2019), we consider a differentiated goods industry. In particular, we compare the R&D investments made by firms under the following market structures: R&D competition without patents, R&D competition with patent protection, R&D cooperation, and full industry cooperation.…”
mentioning
confidence: 99%